2012
DOI: 10.1103/physrevd.86.083507
|View full text |Cite
|
Sign up to set email alerts
|

Confronting MOND and TeVeS with strong gravitational lensing over galactic scales: An extended survey

Abstract: The validity of MOND and TeVeS models of modified gravity has been recently tested by using lensing techniques, with the conclusion that a non-trivial component in the form of dark matter is needed in order to match the observations. In this work those analyses are extended by comparing lensing to stellar masses for a sample of nine strong gravitational lenses that probe galactic scales. The sample is extracted from a recent work that presents the mass profile out to a few effective radii, therefore reaching i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 50 publications
1
26
0
Order By: Relevance
“…It has been shown to reproduce flat rotation curves of spiral galaxies without the need for DM, and naturally predicting the observed relation between galaxy rotation and luminosity (Tully & Fisher 1977;Sanders & McGaugh 2002) or baryonic mass (McGaugh 2012). Only a few MOND analyses have been carried out on early-type galaxies (ETGs; e.g., Cardone et al 2011;Ferreras et al 2012;Milgrom 2012;Sanders 2014). Recently, Tortora et al (2014c) have demonstrated that MOND is consistent with the central dynamics of ETGs if the stellar M/L are systematically larger in higher-velocity dispersion (σ) galaxies, when compared with those calculated from stellar populations, assuming a universal stellar IMF.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown to reproduce flat rotation curves of spiral galaxies without the need for DM, and naturally predicting the observed relation between galaxy rotation and luminosity (Tully & Fisher 1977;Sanders & McGaugh 2002) or baryonic mass (McGaugh 2012). Only a few MOND analyses have been carried out on early-type galaxies (ETGs; e.g., Cardone et al 2011;Ferreras et al 2012;Milgrom 2012;Sanders 2014). Recently, Tortora et al (2014c) have demonstrated that MOND is consistent with the central dynamics of ETGs if the stellar M/L are systematically larger in higher-velocity dispersion (σ) galaxies, when compared with those calculated from stellar populations, assuming a universal stellar IMF.…”
Section: Introductionmentioning
confidence: 99%
“…See also [37] and [38]. More recently, a survey on confronting MOND/TeVeS with strong gravitational lensing over galactic scales has been performed in [60]. The conclusion is that in order to accommodate all observations, a dark matter component is needed even in the MOND/ TeVeS framework.…”
Section: Alternatives To Dark Mattermentioning
confidence: 99%
“…The initial velocity of χ relative to the detector in question, denoted by v, is dominated by the galactic rotation of the solar system which is about 220 km/s. 60), 61) So the process can be treated 60) Note that the earth orbital speed is about 30 km/s and the maximal tangential speed due to the rotation of Earth around its axis is about 0.5 km/s. So to our lowest order estimate we neglect the earth motion.…”
Section: A Cursory Look Of the Basic Formulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides these numerous big problems, a long list of fundamental physics difficulties such as violating the conservation of momentum exist in MOND theory [29]. The relativistic version of MOND theory (TeVeS) is also not supported by recent gravitational lensing results in clusters [30].…”
Section: A Introductionmentioning
confidence: 99%